Traditional Culture: “Small” Wooden Temples of the Russian North - Permilovskaya, Anna (project baikal, 2021)
Wooden chapels are a bright and typical phenomenon of the traditional culture. The chapels were non-altar temples of a small peasant parish, which retained their independence, providing a special atmosphere for performing rituals. The work examines the reasons for setting chapels according to historical and typological characteristics and the specifics of the formation of their architectural and structural features. The empirical base of the research was the material of 36 architectural and ethnographic expeditions, archival and museum sources of the Arkhangelsk and Vologda regions, Karelia, Moscow, St. Petersburg, NAO.
Keywords: Russian North; chapel; wooden architecture; traditional culture; chapel’s typology